Photovoltaic Power Generation System Utilizing Temporary Error Compensation and Photovoltaic Array Failure Detection - Sun, Kiju; Cheon, Minwoo (Transactions on electrical and electronic materials, 2019)
Recently, as new and renewable energy has been actively supplied, numerous photovoltaic (PV) power generation facilities aimed at constructing zero-energy houses and reducing energy have rapidly developed. In this study, a monitoring device capable of continuously measuring the voltage and temperature data generated by individual PV modules was developed to determine whether a given module is abnormal. To examine the operating characteristics of the developed PV module monitoring device, a 3-kW PV power generation facility was built to conduct a comparative analysis of the changes in the voltage, current, and temperature between the normal group and the abnormal group. As a result, it was possible to determine whether each module was abnormal based on changes in the voltage and temperature measured using the developed monitoring device. Since a simply structured module monitoring device was used to determine whether a PV module was abnormal without using digital algorithms, it was expected that this monitoring device would be applicable to small-scale PV power generation facilities.